Restoration and Recovery of Shallow Eutrophic Lake Ecosystems in the Netherlands 1992
DOI: 10.1007/978-94-011-2432-4_26
|View full text |Cite
|
Sign up to set email alerts
|

Restoration and recovery of shallow eutrophic lake ecosystems in The Netherlands: epilogue

Abstract: During the symposium 'Restoration and recovery of shallow lake ecosystems in The Netherlands' studies on restoration of eutrophic lakes were addressed and discussed. Many Dutch shallow lakes have received high external loadings of phosphorus through supply water that is influenced by the River Rhine and loadings in The Netherlands. Two important Action Plans (the Rhine Action Plan, the North Sea Action Plan) are now in operation to reduce nutrient emissions. The targets set are not likely to be fully reached, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
0
14
1
1
Order By: Relevance
“…Previous studies have shown that the water quality of eutrophic freshwater lakes has failed to improve despite a drastic reduction in external contaminant loading because of increased internal loading from the sediments (Sas 1989;Van Liere and Gulati 1992;Istvánovics and Somlyódy 2001;Lai and Lam 2008). However, our results suggest that the internal loading may be even more significant in the case of Saemangeum Lake.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies have shown that the water quality of eutrophic freshwater lakes has failed to improve despite a drastic reduction in external contaminant loading because of increased internal loading from the sediments (Sas 1989;Van Liere and Gulati 1992;Istvánovics and Somlyódy 2001;Lai and Lam 2008). However, our results suggest that the internal loading may be even more significant in the case of Saemangeum Lake.…”
Section: Discussioncontrasting
confidence: 78%
“…Large shallow lakes, in particular, have received attention in special symposia in Europe (e.g., Van Liere & Gulati, 1992), and now in Asia (this special issue). Such lakes contain a large percentage of the world's fresh water, provide ecosystem services to hundreds of millions of people, and are located in areas prone to anthropogenic and climactic impacts.…”
Section: Discussionmentioning
confidence: 99%
“…For such shallow lakes in the Netherlands, e.g. Loosdrecht lakes (Van Liere and Gulati, 1992), the failure of restoration studies is partly attributed to the wind-induced turbid conditions, i.e. poor light climate to which cyanobacteria are well adapted.…”
Section: Prevention Of Sediment Resuspensionmentioning
confidence: 99%